Bifidobacterium lactis TY-S01 Prevents Loperamide-Induced Constipation by Modulating Gut Microbiota and Its Metabolites in Mice - Tang, Tian; Wang, Jing; Jiang, Yuanyuan; Zhu, Xu; Zhang, Zhen; Wang, Yuying; Shu, Xi; Deng, Yadan; Zhang, Feng (Frontiers in Nutrition, 2022)
Probiotics have received widespread attention as a healthy ingredient. The preventive effect of Bifidobacterium lactis TY-S01 on loperamide-induced constipation in mice was investigated in this study. TY-S01 accelerated the peristalsis of intestine, maintained the humidity of faeces, prevented the destruction of gut barrier and remained the 5-HT, MTL and SP at normal levels in constipated mice. Simultaneously, TY-S01 up-regulated the mRNA expressions of 5-HT4R, SERT and MUC-2 while down-regulated the mRNA expressions of pro-inflammatory genes remarkably. The levels of SCFAs in feces of constipated mice were also increased because of the intervention with TY-S01. Moreover, TY-S01 prevented gut microbiological dysbiosis in constipated mice. Spearman’s correlation analysis revealed that there was obvious association between metabolic biomarkers and gut microbiota. In summary, TY-S01 regulated gut microbiota and the production of intestinal metabolites to prevent loperamide-induced constipation.